Bimbingan Kelompok Teknik Diskusi Dalam Meningkatkan Motivasi Belajar Siswa - Adela, Nurul; Karneli, Yeni; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Learning motivation is a crucial factor in the success of the educational process, serving as the primary driver that encourages students to start, sustain, and complete learning activities. This study aims to examine the effectiveness of implementing group guidance with discussion techniques in enhancing students’ learning motivation. The method used is a literature review by referring to various sources such as books, journals, and other scholarly literature. The findings indicate that group guidance using discussion techniques positively impacts the improvement of students’ learning motivation. This is supported by previous studies showing a significant increase in students’ motivation scores after participating in group discussion activities. Moreover, the discussion process, which involves active interaction among members, helps students develop social skills, deepen conceptual understanding, and foster positive attitudes towards learning. In conclusion, group guidance with discussion techniques can be an effective strategy for educators to boost learning motivation, especially among adolescent students in secondary education.